2022
DOI: 10.1021/acs.jafc.2c05144
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Activity of Novel Laccase Inhibitors as Fungicides against Rice Blast

Abstract: Laccase is a potential target for novel agricultural fungicide discovery. PMDD-5Y was the first agent reported with high activity against laccase to control phytopathogenic fungi. Thirty-two novel agents containing cinnamaldehyde thiosemicarbazide were synthesized with PMDD-5Y as the lead compound, with most of the target compounds exhibiting excellent activity in vitro. Compound a2 (EC50 = 9.71 μg/mL) exhibited greater potency against Magnaporthe oryzae than the commercial fungicide isoprothiolane (EC50 = 18.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The in vitro fungicidal activities of all target compounds against five economically important phytopathogenic fungi were conducted based on the previously reported mycelium linear growth rate method . The in vitro bioassays, as listed in Table , indicated that at 40 mg/L, a few compounds exhibited good fungicidal activity against R.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The in vitro fungicidal activities of all target compounds against five economically important phytopathogenic fungi were conducted based on the previously reported mycelium linear growth rate method . The in vitro bioassays, as listed in Table , indicated that at 40 mg/L, a few compounds exhibited good fungicidal activity against R.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro fungicidal activities of all target compounds against five economically important phytopathogenic fungi were conducted based on the previously reported mycelium linear growth rate method. 15 The in vitro bioassays, as listed in Table 1, indicated that at 40 mg/L, a few compounds exhibited good fungicidal activity against R. solani, B. cinerea, P. capsica, and F. graminearum and over one-third of these compounds exhibited moderate to considerable fungicidal activity against R. solani and B. cinerea, which were much higher than that of the natural product, aspernigerin. In particular, compounds 1h, 2b, 2i, 3j, and 3m exhibited excellent activities against R. solani, and 1h, 2i, and 3j exhibited excellent activities against B. cinerea with more than 80% inhibition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant pathogenic fungi can cause a variety of plant diseases, which have been a major threat to crop production. [1] The pathogens plunder a large amount of nutrients and seriously hinder the normal growth of host plants, imposing a great destructive effect on the production of various crops. [2,3] Apple ring rot is a serious disease of apple trees caused by the infection of Botryosphaeria dothidea, which mainly infect apple branches and fruits, resulting in the ring-shaped rots on apple fruits as well as the warts and ulcers on stem epidermis.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-laccase assay results showed that the active compounds were excellent laccase inhibitors. [14][15][16] Maniak et al synthesized a series of new phenolic hydrazide-hydrazones. The laccase inhibitory assay results and the docking study suggested that the target compounds could be potential laccase inhibitors.…”
Section: Introductionmentioning
confidence: 99%